Expressões estrangeiras em língua portuguesa e avanços tecnológicos: Um estudo histórico-linguistico da seção tem mensagem pra você da revista info exame - Silva, Antonio Carlos Pinho (2005)
The purpose of this Dissertation is to study foreign phrases in the Portuguese language resulting from the globalization process. Due to economic, social, political, and cultural changes caused by globalization and the civilizing process, the Portuguese language used in Brazil has been continuously influenced by foreign phrases over the past decades. In this research, we intend to examine, using a historical linguistic approach, foreign phrases, particularly English loanwords, found in the section Tem mensagem para Você ( You ve got a Message ) of the Info Exame magazine, and linguistically, historically, and politically incorporated into Brazilian Portuguese. To this end, we resorted to Linguistic Historiography for theoretical/methodological support, which allowed us to realize the borrowings into our language. In the course of the research, we tried to examine the set of conscious choices made in the domain of relations between language and society, and more particularly, between language and national life, in order to accept the presence of foreignisms as a matter of linguistic policy. Therefore, we found that the adoption of foreign phrases into Portuguese result from historical factors and the socio-cultural scene due to the influences of globalization and the civilizing process. Based on our reviews, we were able to consider that the use of foreign words and phrases has crystallized in Brazilian Portuguese, and such usage reflects the influence of globalization, especially considering the information technology advances. The theoretical/methodological basis appears adequate as it enabled us to verify that language, when undergoing changes induced by internal and external aspects, naturally borrows foreign terms and phrases under the influence of globalization. Thus, the use of foreignisms triggers linguistic innovations and adoptions in a language due to the undeniable force of information technology. Finally, we verified that interdisciplinarity between History and Linguistics ensured the achievement of the overall goal of our research.